Asthma exacerbations · 2: Aetiology - Singh, A M (BMJ Group, 2006)
The natural history of asthma involves relatively stable periods that are often punctuated by significant exacerbations of symptoms. There are many aetiologies that may lead to an increase in asthma severity including respiratory infection (bacterial/viral), allergens, irritants, and occupational exposures. Each trigger probably acts through different mechanisms, but a final common pathway of multicellular inflammation, enhanced bronchial responsiveness, and airflow obstruction is a likely consequence. This review discusses the most common causes of asthma exacerbations with a focus on their microbiology and immunopathogenesis. Through an understanding of underlying causes of asthma exacerbations, treatments with increased effectiveness may be developed, and it is these future developments that may directly influence the morbidity and mortality of the disease.